The Theory of Accountability and Freedom in the View of the Judge, Abdul-Jabbar - Hawre Omar Awle; Saadoon Hussein Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
According to Judge Abdul-Jabbar, the theory of accountability and freedom falls within the origin of the second of the Islamic five fundamentals agreed upon by the Mu’tazilites in their theological doctrine, justice. Without acknowledging the two principles of accountability and freedom, justice cannot be addressed as Judge Abdul-Jabbar believes, who goes furthers and finds accountability the reason of man creation. Man is divided into mental accountability and judicial accountability, and the former takes precedence over the latter. Therefore, the human being is authorized even before the divine message, because the message comes in supporting and detailing what the mind decides of duties and rights. Man’s freedom is among the rights that are determined in the mind and acknowledged by the law. Then it is not possible to talk about divine justice without proving accountability and freedom and that accountability is not true without identifying freedom for man’s action. Thus, man becomes responsible for his voluntary actions, and in the end reward and punishment are truly in accordance with divine justice.